ANALISIS PEMASARAN KARET (Hevea brasiliensis ) DI DESA PULAU SARAK KECAMATAN KAMPAR KABUPATEN KAMPAR - Riska Anggrianti; Shorea Khaswarina; Eliza Eliza (Fakultas Pertanian, Universitas Riau, 2021)
Research on Rubber Marketing Analysis (Hevea Brasiliensis) in Sarak Island Village Kampar Sub-district Kampar Regency aims to (1) know the marketing channel of rubber (2) analyze cost, margin, profit and farmer share, (3) analyze the efficiency level of rubber marketing in Sarak Village village Kampar Kampar District. The research was conducted on October 2017 until May 2018, The method used survey method with purposive sampling sampling with criterion of farmer who have wide of land of 1-2 hectare, taken samples counted 35 farmer, sampling of merchant conducted by snowball sampling method. The result of the research is 3 marketing channel of rubber that is marketing channel 1 from farmer to collecting merchant to factory, marketing channel 2 from farmer to collecting trader, wholesaler and to factory, marketing channel 3 from farmer to Joint Business Group then to factory. Marketing channel I obtained total marketing cost Rp1.568 / kg, total marketing margin of Rp1.549 / kg, and marketing profit of Rp791 / kg and farmer share of 83.10 percent. Marketing channel II obtained total marketing cost Rp1,807.45 / kg, total marketing margin of Rp1.585 / kg, and marketing profit of Rp634 per kg and farmer share of 82.71 percent. Marketing channel III obtained total cost Rp1.386 / kg, total marketing margin of Rp600 / kg and marketing profit of Rp150, 25 / kg and farmer share of 93.57 percent. The marketing efficiency of marketing channel I is 17.10 percent, marketing channel II marketing efficiency of 19.71 percent, and marketing channel III marketing efficiency of 14.86 percent.